Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/anie.201308533
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Hybrid Protein Zymogens through Protective Dendritic Assembly

Abstract: The modulation of protein uptake and activity in response to physiological changes forms an integral part of smart protein therapeutics. We describe herein the self-assembly of a pH-responsive dendrimer shell onto the surface of active enzymes (trypsin, papain, DNase I) as a supramolecular protecting group to form a hybrid dendrimer-enzyme complex. The attachment is based on the interaction between boronic acid and salicyl hydroxamate, thus allowing the macromolecular assembly to respond to changes in pH betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 23 publications
0
85
0
1
Order By: Relevance
“…190 The ratio of the conjugated dendrimers to antibodies rather than the size affected the binding affinity of the antibody-dendrimer conjugates to a target. 192 Pro-tease-PAMAM dendrimer conjugates enhanced the cellular uptake 193 and efficiently killed tumor cells. 191 Dendrimer-enzyme conjugates were developed as proenzymes that can be activated in acidic environments.…”
Section: Dendrimersmentioning
confidence: 99%
See 2 more Smart Citations
“…190 The ratio of the conjugated dendrimers to antibodies rather than the size affected the binding affinity of the antibody-dendrimer conjugates to a target. 192 Pro-tease-PAMAM dendrimer conjugates enhanced the cellular uptake 193 and efficiently killed tumor cells. 191 Dendrimer-enzyme conjugates were developed as proenzymes that can be activated in acidic environments.…”
Section: Dendrimersmentioning
confidence: 99%
“…[187][188][189] In addition, protein-cationic dendrimer conjugates, where protonated amines in spermine groups at the surface of dendrimers interact with DNA via electrostatic interaction, transported DNA into cells in vitro. 192 Lysines in proteases, modified with 4-carboxyphenylboronic acid, reacted with salicyl hydroxamates in PAMAM G2 dendrimers to generate protease-PAMAM dendrimer conjugates. 191 The greater the number of dendrimers conjugating to antibodies, the weaker the binding affinity of the conjugates became.…”
Section: Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). A variety of engineered zymogens are currently in development including engineered coagulation cascade proteins, zymoxins, and dendronized proteases [5052]. Zymoxins (engineered zymogen toxins via KBM) are currently an active area of research with significant emphasis on activation by viral proteases for selective killing of virally infected cells.…”
Section: Targeted Drug Activationmentioning
confidence: 99%
“…Also, synthetic pH sensitive zymogens have been constructed by self-assembly of dendrimers onto the surface of trypsin, papain, and DNase I. At near neutral pH, the dendrimers sterically block the normal action of the enzymes, while at reduced pH the dendrimers dissociate, allowing activation of the zymogens [52]. There is growing realization of the importance of ROS signaling for a variety of cellular processes, and a large number of proteins have been identified that are responsive to ROS second messengers such as H 2 O 2 through reversible cysteine oxidation mechanisms [59].…”
Section: Targeted Drug Activationmentioning
confidence: 99%